O celular como dispositivo eletrônico para produção de textos multimidiáticos: de objeto proibido à condição de recurso pedagógico em sala de aula - Arantes, Clécia de Vasconcelos (2015)
This paper presents the results of a school activity that aimed to provide training on reading especially to the production of multisemiotics texts, using cell phones as a teaching device, considering that this instrument, though banned at school, had being used improperly in classroom especially for social networks access, rising up stress and indiscipline. The target group of this study has been a class of 8th grade on an elementary public school in João Pessoa. The investigation process was performed in two steps. The first one, ethnographic featured, enabled us to understand the reasons for which students take cell phone use in classroom, what they think about the ban and which texts are usually used in their interactions on social networks. The second one, an action research, was conducted through the effort of a multiliteracy project, admitting and discussing the linguistic knowledge, based on students’ skills with mobile applications as a start point to improve reading / writing multimediatic texts. Therefore we have made use of the contributions of Lévy (1999), Santaella (2004, 2007, 2009), Guidelines for Mobile Learning UNESCO (2014), ROJO (2009, 2012, 2013), and others. Results indicate that it is essential to shelter social practices diversity on reading and writing, as well as to cultural property produced by contemporary society, which includes mobiles as hybrid, multifunctional and at the same time global connection channel device, through which occur so many languages and cultures. School's role is to develop with students reading and writing skills that will let them be able to assume an ethical and democratic position in contemporary society.